Pathogenic serum IgG anticardiolipin antibodies and the idiotypic network. - Cohen, J (1993)
OBJECTIVES--To determine whether active immunisation of mice with pathogenic anticardiolipin antibodies (IgG and IgM), derived from the serum of a patient with the antiphospholipid syndrome, could dysregulate the idiotypic cascade and induce the production of anti-anti-anti-cardiolipin (Ab3) with anticardiolipin activity by the mice with the association of overt antiphospholipid syndrome. METHODS--Anticardiolipin antibodies were purified from the serum of a patient with the antiphospholipid syndrome. The purified anticardiolipin antibodies were used to immunise mice at the footpads and the mice were then followed up for serological and clinical manifestations of the antiphospholipid syndrome. RESULTS--The IgG anticardiolipin antibody was found to be monospecific and to bind cardiolipin with high affinity. Immunisation of naive BALB/c mice with the purified IgG anticardiolipin antibody was followed by production in the mice of sustained high titres of IgG anticardiolipin antibody, associated with a prolonged activated partial thromboplastin time (64.5 (9.7) v 30.1 (1.7) seconds in control mice) and thrombocytopenia (0.4 (0.06) x 10(9) v 1.0 (0.09) x 10(9)/l platelets in controls). The titres of other autoantibodies (for example, antibodies to DNA, histone), though high after the immunisation, decreased rapidly and were almost undetected one month after the boost injection. The mice immunised with the IgG anticardiolipin antibody showed low fecundity (36% of mice became pregnant v 62% in the group immunised with control IgG). The pregnant mice had an increased resorption rate (the equivalent of fetal loss in the human) of 61 (9)% v 5 (4)% in the control group. The mean (SD) embryo and placental weights in mice with the antiphospholipid syndrome were significantly lower than in the mice injected with control IgG (641 (210) and 103 (14) mg v 1303 (105) and 145 (8) mg respectively. The IgM anticardiolipin antibodies purified from the same patient were found to be polyspecific, binding with low affinity to anticardiolipin antibodies and double stranded DNA, and carried the anti-DNA idiotype 16/6. Mice immunised with the purified IgM anticardiolipin antibodies, though showing reduced fecundity (30%), had only a slightly increased resorption rate (12 (9) v 3 (5)% in controls) and only a slight and statistically non-significant decrease in mean (SD) embryo and placental weights (1134 (188) and 136 (11) mg respectively). CONCLUSIONS--The results confirm the induction of pathogenic anticardiolipin antibodies by immunisation with serum anticardiolipin, dysregulating the idiotypic network, and point to the higher pathogenic potential of serum IgG v IgM anticardiolipin antibodies.